OBSERVATIONS ON THE FLUCTUATIONS IN PROTEIN, FAT AND WATER CONTENT IN CYPRINUS CARPIO (LINN.) IN RELATION TO THE STAGES OF MATURITY - Masurekar, V B; Pai, S R (Indian Journal of Fisheries, 2011)
The muscles of the freshwater fish, Cyprinus carpio were analysed for theirprotein, fat and water content over a period in which the different maturity stagesof the fish weire obtained. The variations in the above mentioned body constituentswere seen to be related to the reiproduction cycle. A gradual depletion wasobserved during maturation, and the least prote.'n and fat content was observedin the spent individuals. Variations were also found in the serum protein patternsin the female in different matudty stages as demonstrated by polyacrylamideelectrophoresis.